Static Model of Zubair Reservoir in Luhais Oil Field - Alher, Ahmed Abdulmueen; Aljawad, Mohammed Saleh; Ali, Abdullah Abdulhasan (Iraqi Journal of Chemical and Petroleum Engineering, 2018)
Static reservoir modeling is the interacting and analysis of the geological data to visualize the reservoir framework by three-dimensional model and distribute the static reservoir properties. The Petrel E&P software used to incorporate the data. The interpreted log data and core report used in distribution of petrophysical properties of porosity, water saturation and permeability for Zubair reservoir in Luhais oil field. The reservoir discretized to 274968 cells in increments of 300, 200 and 1 meter in the direction of X, Y, and Z respectively. The geostatistical approach used in the distribution of the properties of porosity and water saturation overall the reservoir units. The permeability has been calculated with classical method depending on the routine core reports data. The results show the main reservoir unit is 1C where its porosity and permeability are about 20% and 400md respectively. This unit underlaid by barrier unit and rounded by water. The estimated value of oil in place is about 209*106 ScM3, most of it accumulate at 1C unit and the other at the upper parts of unit 1E.